Determinants of Economic Growth in Ghana - Christian Kwasi Darko (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Determinants of economic growth in Ghana are analysed using restricted vector autoregressive (VAR) model for the period 1975-2013. The empirical results reveal that GDP per capita in long-run is driven by export, oil and mineral rents while government consumption retard economic growth. Therefore the dynamic relationship between these variables on economic growth should not be underestimated by policymakers. However, Ghana's economic growth is subject to uncertainty associated with expected risks of price volatility of primary commodities which make a great proportion of the export and the so-called Dutch disease which may hinder economic growth in the long-run.
Keywords: O10; C22; 330; economic growth; export; error correction model; weak exogeneity